Role Of Fintech Adoption on Banking Sector Efficiency: A Survey Based Research Approach - Dr. S. M. Uvaneswaran, Dr. Anand Muley, Rekha Bawa, Parul Verma (Journal of Informatics Education and Research, 2024)
Comparing financial technology businesses during the fourth industrial age to their counterparts, this study investigates the effects of these companies adhering to effective manufacturing practices. The objective is to offer actual proof of the operational effectiveness of FinTech companies and how business efficiency affects market performance. FinTech has to pass through different business models to attain the maturity as a successful pure player actor. This demonstrates that FinTech innovations improve banks' performance using several panel data estimators, including panel-corrected standard errors for linear regression, fixed effects, and random effects. Furthermore, it also show that the proportion of capital that is adequate, earnings capacity, total assets, and yearly GDP growth rate of banks also have a noteworthy beneficial influence on bank performance. By using a balanced scorecard to examine financial points of view, customer perspectives, business internal perspectives, education and growth perspectives, and competitive advantage in services growth and development, monetary advantage, and economic inclusion when implementing FinTech, this study seeks to understand the impact of these factors on banks' performance. A sample of 259 respondents was collected from people working in banking sector. The variables that identify the role of Fintech adoption on banking sector efficiency are Financial Inclusion, Data Analytics and Insights, Cost Reduction, and Improved Customer Experience.